ANALYSIS OF WAREHOUSE OPERATIONAL EFFECT ON ITS DISTRIBUTION EFFECTIVENESS IN PT ARTA BOGA CEMERLANG IN TANGERANG - Irawan, Roy (Journal of Research in Business, Economics, and Education, 2019)
Proper operation can affect how the company is able to distribute goods running well can also be determined how effective distribution of the goods is carried out. With the operations of a company can carry out their respective functions and roles to produce output in the form of goods and services. Especially hypermarkets and minimarkets in the Greater Jakarta area. This research uses the observation method, literature study method, and questionnaire method. This study uses the Product Moment correlation formula (Corrected Item-Total Correlation) consisting of: correlation coefficient, coefficient of determination and regression equation, and t test results. The results of this study indicate that between warehouse operations and the effectiveness of the distribution of goods there is a very strong relationship with a correlation coefficient of 0.865, while for the calculation of the determination obtained 74.8% results, which means that 74.8% influence of warehouse operations on the effectiveness of the distribution of goods and the rest of 25.2% is influenced by other factors and it is concluded that if there is an increase in warehouse operations, the value of the effectiveness of the distribution of goods will increase or increase.